Efektifitas Ekstrak Nannochloropsis oculata Terhadap Peningkatan Kepadatan Kolagen pada Proses Penyembuhan Alveolar Osteitis. - Ajeng Saghita Enggardini; Syamsulina Revianti; Noengki Prameswari (Denta Journal Kedokteran Gigi, 2016)
Background: Alveolar osteitis was one complication after tooth extraction. This conditionremains a common post operative problem that results in severe pain and inhibit sockethealing. Nannochloropsis oculata’s extract contains alkaloids, carotenoids, flavonoids,terpenoids and tocopherols that could accelerate the wound healing process. Purpose: Examine the effectivity of Nannochloropsis oculata extract to the increased density ofcollagen in alveolar osteitis healing process. Materials and Methods: This research designwas post-test only control group design, using 64 male Wistar rats then divided into twomajor groups. Group 1 (irrigation) and group 2 (dressing). In each group contains a negativecontrol group (irrigation PBS or dressing PBS), positive control group (irrigation Saline0,9% or dressing Alvogyl), and the treatment group (irrigation or dressing usedNannochloropsis oculata extract 2,5% and 5%). After treatment on the 3rd and 7th day, ratswere euthanazied than collagen density was measured at histopathology slide used Masson’sTrichom with magnification 100x under light microscope, than it what measured. Data wasanalyzed with Kruskal-Wallis and Mann-Whitney test. Result: There were significantdifferences of collagen density beetwen irrigation treatment groups (0,045), but there werenot significant differences beetwen dressing treatment groups (0,243). Dressing method wasmore effective to increase collagen density than irrigation groups (0,026). Conclusion:Dressing treatment used Nannochloropsis oculata extract concentration 5% was mosteffective to increased the collagen density in alveolar osteitis healing process on 7th days.